Bernard Chazelle: Natural Algorithms - Lipton, Richard J; Regan, Kenneth W (People, Problems, and Proofs, 2013)
This chapter describes Chazelle’s concept of “Natural Algorithms” amid other uses of “natural” in mathematics and computer science. A theorem of his about equilibria in Nature exposes some of the ideas.